Clinical spectrum and carrier state of nontyphoidal salmonella infections in infants and children - Kazemi, M. (1974)
A study was done of 117 children with nontyphoidal salmonellosis from the clinic and inpatient populations of The Montreal Children's Hospital. Uncomplicated gastroenteritis was the most common clinical presentation and the mean duration of illness was 8.7 days. Eleven (24%) of 45 patients tested had bacteremia; retrospective analysis of these patients did not reveal major differences in clinical presentation, laboratory findings, underlying disease or complications when compared with the patients from whom blood cultures were not taken. There were no complications in any of the patients and no deaths. Prolonged stool carriage beyond eight weeks was not a problem except in infants under the age of 3 months, of whom 27% were carriers eight weeks after the onset of illness. Antibiotic therapy was not effective in treating the acute illness and seemed to prolong carriage in young infants.